Konflik Antar Agama, Resolusi dan Rekonsilasi - Husna Hanifah; Fadhilah Ikhwani; Sahdin Hsb (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Religion is a fundamental belief that influences human attitudes and behavior in social life. However, differences in beliefs often trigger conflict, especially in a pluralistic society such as Indonesia, which has a diversity of religions, ethnicities, races, and cultures. Religious conflicts are often understood negatively and resolved destructively, thereby potentially disrupting social harmony. This study aims to analyze conflicts of belief in multicultural societies and examine the importance of conflict resolution and reconciliation as efforts to build religious tolerance. The research method used is a qualitative approach with a literature study, through the collection and analysis of various relevant scientific sources. The results of the study show that religious conflicts can be resolved constructively through the internalization of tolerance values, multicultural education, the rejection of identity politics, and inclusive leadership. In conclusion, conflict resolution based on cultural values and education plays an important role in shaping a generation that is capable of becoming agents of peace and maintaining the integrity of Indonesia.